Effect of continuous hemofiltration on severe acute pancreatitis with different intra-abdominal pressure: A cohort study. Issue 44 (5th November 2021) - Xie, Yongle; Yuan, Yuan; Su, Wentao; Qing, Nan; Xin, Hongwei; Wang, Xiaoying; Tian, Jing; Li, Yun; Zhu, Junnian
Abstract: Background: The clinical efficacy and timing of continuous veno-venous hemofiltration (CVVH) in the treatment of severe acute pancreatitis (SAP) remain uncertain. In this prospective cohort study, patients with SAP were classified according to intra-abdominal pressure (IAP). Methods: Seventy-four patients with SAP admitted to the intensive care unit were randomly divided into group A (IAP ≥20 mm Hg) and group B (with IAP ⩽20 mm Hg). Then, according to whether CVVH was administered or not, groups A and B were divided into 4 subgroups: group A1 and B1 (non-CVVH treatment), group A2 and B2 (CVVH treatment). Changes in clinical and laboratory indicators were recorded before and on the seventh day after treatment, and clinical outcomes were analyzed. Results: Before treatment, there was no significant difference in general conditions between subgroups A1 and A2, and between subgroups B1 and B2. After CVVH treatment, the indicators recorded in group A2 were significantly improved compared to those in group A1 ( P < .05). In group A2, the 28 day operation rate was lower ( P < .05), as mechanical ventilation, gastric decompression, and intensive care unit treatment time were shorter ( P < .05). However, there was no statistically significant difference in any of the above indicators between subgroups B ( P > .05). Groups A2 and B2 had more days of negative fluid balance within 1 week of admission than groups A1 and B1 ( P < .05). Conclusions: For SAP, patients with IAP ≥20 mm Hg can benefit from treatment with CVVH, but for patients with IAP ⩽20 mm Hg, the efficacy is not clear, and monitoring IAP may be an indicator to decide whether or when to initiate CVVH. Negative fluid balance caused by CVVH treatment may be one of the reasons for the benefit of this group of patients.